Medical Computer Vision: recognition techniques and applications in medical imaging (1st MICCAI-MCV workshop) - Menze, B.; Langs, G.; Tu, Z.; Criminisi, A.; Criminisi, Antonio (Springer, 2011)
The Workshop on Medical Computer Vision (MICCAI-MCV 2010) was held in conjunction with the 13th International Conference on Medical Image Computing and Computer – Assisted Intervention (MICCAI 2010) on September 20, 2010 in Beijing, China. The one-day workshop focused on recognition techniques and applications in medical imaging. The participants discussed principled approaches that go beyond the limits of current model-driven image analysis,which are provably eﬃcient and scalable, and which generalize well to previously unseen images. It included emerging applications that go beyond the analysis of individual clinical studies and speciﬁc diagnostic tasks – a current focus of many computational methods in medical imaging. The workshop fostered discussions among researchers working on novel computational approaches at the interface of computer vision, machine learning, and medical image analysis. It targeted an emerging community interested in pushing the boundaries of what current medical software applications can deliver in both clinical and research medical settings. Our call for papers resulted in 38 submissions of up to 12 pages each. Each paper received at least three reviews. Based on these peer reviews,weselected10 submissions for oraland11 for poster presentation. The Best Scientiﬁc Paper Award was given to Michael Kelm and co-authors fortheir contribution“Detectionof3DSpinalGeometryUsing Iterated Marginal Space Learning.” The runners-up were Peter Maday and co-authors for their contribution “Imaging as a Surrogate for the Early Prediction and Assessment of Treatment Response Through the Analysis of 4-D Texture Ensembles,” and Dongfeng Han and co-authors for their contribution “Motion Artifact Reduction in 4D Helical CT: Graph-Based Structure Alignment.” During the workshop two distinguished invited speakers oﬀered their perspective on the development of the ﬁeld: Dorin Comanicu of Siemens Corporate Research, and Yiqiang Zhan of Siemens Medical Solutions.
Workshop held in conjunction with MICCAI 2010, Beijing, China.